For the first question, a reminder that the change of base formula goes as follows:
log[base c](a) = {log[base b](a)} / {log[base b](c)}
Translation: You can turn a single log into a quotient of logs by choosing whatever base you wish.
Since we want the base of our log to be calculator friendly, you can choose b = 10. Then
Log [base 9] (61.31) = [log (61.31)] / [log (9)]
Another calculator friendly base would be e, resulting in taking the natural log, ln.
Log [base 9] (61.31) = ln (61.31) / ln (9)
To solve the equation
log[base 4](x-4) + log[base 4](x-4) = 1
First note that those two terms are exactly the same. So we can combine them since they are like terms.
2 log [base 4](x - 4) = 1
A reminder that log[base b](a^c) = c * log[base b](a). Therefore,
log[base4](x-4)^2 = 1
Now, we convert this to exponential form.
4^1 = (x-4)^2
4 = x^2 -8x + 16
x^2 - 8x + 12 = 0
Therefore, (x - 6)(x - 2) = 0
So x = 6 or x = 2
BUT WAIT! You can't assume those values will work; you have to test the values in the original function, and if you end up taking the log of a negative number, you discard it.
Test x = 6: log[base 4] (6 - 4) + log[base4](6-4) checks out.
Test x = 2: log[base 4] (2 - 4) ..... this one already fails.
Therefore, x = 6 is the only answer.
2006-12-08 12:54:43
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
most calculators or available logarithm tables only provide base e or base 10 logarithms. so use the change of base rule
to calculate the base b log of any number x using base 10 logs:
logb x = (log10 x) / (log10 b)
for the given problem, this is:
log9 61.31 = log10 61.31 / log10 9 =
1.7875 / 0.9542 = 1.8732
to verify, raise 9 to the power of 1.8732
-------------
1 apple + 1 apple = 2 apples, so
log4(x-4) + log4(x-4) = 2log4(x-4) = 1
divide both sides by 2, then take the base 4 antilog (raise 4 to the power of each side)
x-4 = 4^(1/2) = +/- 2
add 4 to both sides
x = 4+/-2
x = 6, x = 2
however x=2 is an invalid answer to the original equation if
the log function is restricted to the reals
2006-12-08 12:58:21
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
The change of bases rule is:
log[b] (n) = log(n) / log(b)
So figure:
log(61.31) / log(9)
≈ 1.78753132 / 0.954242509
≈ 1.87324637
which gets rounded to:
1.8732
PART 2:
Original equation:
log[4] (x - 4) + log[4] ( x - 4) = 1
Add the logs which are exactly the same:
2 log[4] (x - 4) = 1
Divide both sides by 2:
log[4] (x - 4) = 1/2
Now raise both sides upon the base 4:
x - 4 = 4^(1/2)
4^(1/2) is the same as sqrt(4) so the answers are ±2
x - 4 = ±2
Add 4 to both sides:
x = 4 ± 2
Simplify:
x = 2 or x = 6
However, you never take the log of a negative number, so 2 isn't a valid answer. Therefore x = 6.
2006-12-08 12:52:20
·
answer #3
·
answered by Puzzling 7
·
0⤊
0⤋
Change of base can work for the first one, but here's another way that I like to do it:
Set log(base 9)[61.31] = x
Change from log form to exponential form: 9 ^ x = 61.31
Take the log of both sides: log[9 ^ x] = log[61.31]
Bring down the x via a log property: x * log[9] = log[61.31]
And divide both sides by log[9]: x = log[61.31] / log[9]
And so x is approximately 1.8733
2006-12-08 13:47:03
·
answer #4
·
answered by chrono803 1
·
0⤊
0⤋
First, we'll let e = the distance traveled by elephant and c = the distance traveled by chariot. We will also let x = the time spent on the elephant and y = the time spent on the chariot. Since neither the camp nor the outskirts of Rome are moving, we know the distance is constant. Therefore, e=c . Also, since Distance = Rate x Time (the "dirt" rule), we know that: e=2x and c=10y We also know that: x+y=18 If we set e and c equal, we get: 2x=10y, or y=x/5 (by dividing both sides by 10) If we set the second equation in standard form, we get y=18-x (by subtracting x from both sides) Now that we have y set to two expressions of x, we can set those expressions equal (this is known as substitution): x/5=18-x Multiply both sides by 5, and we get x=90-5x . Add 5x to both sides, and we get 6x=90 and x=15 (by dividing both sides by x). Take x all the way back and plug it into e=2x, and we end up with e=30. The distance from camp to the outskirts of Rome is 30 km. You can check your work by solving for y using x, which gives y=3. Plug 3 into the equation for c, and you get c=30=e.
2016-05-22 21:45:56
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
log_9 61.31=x
61.31=9^x
ln 61.31=x ln 9
x=log_9 61.31=ln 61.31 / ln 9=1.8732
log_4 (x-4)+log_4(x-4)=1
2 log_4(x-4)-1
log_4(x-4)=.5
x-4=4^.5=2
x=6
2006-12-08 13:17:55
·
answer #6
·
answered by yupchagee 7
·
0⤊
0⤋
not to positive about the first one but i think it's 58.5046
The second one is -3.6124
2006-12-08 12:53:03
·
answer #7
·
answered by Anonymous
·
0⤊
1⤋